Natural and microclonal reproduction of the Dagestan paleoendemic Scabiosa gumbetica Boiss. - A. I. Adzhieva; Z. M. Alieva; V. K. Martemyanova (Юг России: экология, развитие, 2022)
Aim. As a paleoendemic petrophilic species of the foothills of Dagestan Scabiosa gumbetica Boiss, its comprehensive studies are relevant. This work is devoted to the identification of the state of the Tantari cenopopulation of the species and the study of the renewal potential of individuals in the field, in laboratory conditions and through in vitro culture.Material and Methods. Long‐term population studies of Scabiosa gumbetica using geobotanical methods were carried out in the vicinity of the village of Tantari in the Gumbetovsky district of Dagestan. The vital state of individuals was determined by the Zlobin method, while the degree of vitality of individuals was determined according to Ishbirdin. The introduction of the subject into in vitro culture was done according to the generally accepted methodology.Results. A wide range of variation in the characteristics of S. gumbetica individuals characterises the differentiation of ecotopes in which it occurs. The vital analysis of individuals revealed depressive tendencies in the development of the cenopopulation with a low degree of severity. A high value of potential and a low value of real seed productivity were shown – insufficient for successful seed renewal in natural populations. The potential of vegetative renewal of individuals was confirmed, which compensates for the low productivity of natural seed renewal. A scheme of clonal micro‐multiplication of S. gumbetica was developed by cultivating nodal explants on a Murashige‐Skuga medium with the addition of IBA, NAA, BAP and kinetin.Conclusion. Low real seed productivity and depressive tendencies of the vitality of individuals in the Tanari cenopopulation of S. gumbetica indicate the need to develop methods for its conservation. Biotechnological methods can be promising. Studies have substantiated and demonstrated the possibilities of microclonal reproduction by direct organogenesis.